Cannabis in Psychiatric Practice A Practical Guide - Riggs, Paula; Thant, Thida; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book educates and familiarizes psychiatrists with the impact of cannabis beyond the scope of addiction and ways to effectively discuss the existing literature and knowledge with patients. Cannabis in Psychiatric Practice is organized by clinical setting to help tailor the literature to psychiatrists and other mental health clinicians working in all areas, whether traditional outpatient clinics, emergency departments, inpatient psychiatry or medical units. It helps readers, regardless of their training background, learn about the impact of cannabis on a variety of disorders in a manner adjusted to the unique needs and challenges of their particular treatment settings and patient populations. The book also includes clinical cases and practical tips integrating the current evidence, treatment approaches, and psychoeducation needed to effectively practice in the era of modern-day psychiatry and cannabis legalization. Chapters are written in a clear, easy-to-read style, allowing readers to reference specific portions of the book as needed, increasing its utility for the general psychiatrist and mental health clinician. With the increasing prevalence and availability of cannabis and CBD products, this book is an invaluable reference for psychiatrists who wish to explore the impact of cannabis in their clinical practice.
1. Public Health Concerns of Cannabis -- 2. Clinical Pharmacology of Cannabinoids -- 3. Cannabidiol: Overview, Complexities and Opportunities for Behavioral Health -- 4. Developmental Impact -- 5. Cannabis in the Child and Adolescent Outpatient Mental Health Setting -- 6. Cannabis in The Child and Adolescent Emergency and Inpatient Psychiatric Settings -- 7. Clinical Considerations for Cannabis in the Child and Adolescent Consultation-Liaison Setting -- 8. Disease course & prognosis -- 9. Evaluation of Co-occurring Psychiatric Disorders and Cannabis Use in the Outpatient Setting -- 10. Treatment of Co-occurring Psychiatric Disorders and Cannabis Use in the Outpatient Setting -- 11. Acute intoxication and agitation/violence -- 12. Cannabis and Psychosis -- 13. Self-Harm and Cannabis Use -- 14. Cannabis in the Adult Medical and Consultation-Liaison Settings -- 15. Cannabis in the Perinatal Period -- 16. Cannabis in the Geriatric Population -- 17. Marijuana Use in Organ Transplantation.
Keywords: Psychiatry; Psychiatry; Mental Disorders -- drug therapy; Cannabinoids -- therapeutic use; Medical Marijuana -- therapeutic use; Psychopharmacology -- methods